Accuracy of the FAMACHA© method in ewes fed different levels of crude protein - Francisco de Assis Fonseca de Macedo; Fábio José Lourenço; Graziela Aparecida Santello; Elias Nunes Martins; Natália Holtz Alves Pedroso Mora; Alexandre Agostinho Mexia (Acta Scientiarum. Animal Sciences, 2014)
The accuracy of the FAMACHA© method was evaluated on the identification of female sheep fed two levels of crude protein, naturally infected with Haemonchus contortus, by means of the correspondent hematocrit value. Forty-seven female sheep of the breeds Santa Inês (n = 16), Texel (n = 16) and Ile de France (n = 15) aged between eight and twelve months were assigned to two treatments, 12 or 16 % crude protein in the diet. All the animals were wormed thirty days before the first data collections, which were done fortnightly between July 2005 and March 2006. The color of the ocular conjunctiva was individually evaluated according to the precepts of the FAMACHA© method and the hematocrit value of each animal was obtained in laboratory. A correlation of 1:0.7991 was found between the hematocrit values and the classification given by the FAMACHA© method aiming to identify animals with different degrees of anemia. The method was efficient to identify animals to worm, thus representing a support in the identification of animals susceptible to Haemonchus contortus.